Accuracy of Parenchymal Cerebral Blood Flow Measurements Using Pseudocontinuous Arterial Spin-Labeling in Healthy Volunteers - Ambarki, K. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: The arterial spin-labeling method for CBF assessment is widely available, but its accuracy is not fully established. We investigated the accuracy of a whole-brain arterial spin-labeling technique for assessing the mean parenchymal CBF and the effect of aging in healthy volunteers. Phase-contrast MR imaging was used as the reference method. MATERIALS AND METHODS: Ninety-two healthy volunteers were included: 49 young (age range, 20–30 years) and 43 elderly (age range, 65–80 years). Arterial spin-labeling parenchymal CBF values were averaged over the whole brain to quantify the mean pCBF(ASL) value. Total CBF was assessed with phase-contrast MR imaging as the sum of flows in the internal carotid and vertebral arteries, and subsequent division by brain volume returned the pCBF(PCMRI) value. Accuracy was considered as good as that of the reference method if the systematic difference was less than 5 mL/min/100 g of brain tissue and if the 95% confidence intervals were equal to or better than ±10 mL/min/100 g. RESULTS: pCBF(ASL) correlated to pCBF(PCMRI) (r = 0.73; P < .001). Significant differences were observed between the pCBF(ASL) and pCBF(PCMRI) values in the young (P = .001) and the elderly (P < .001) volunteers. The systematic differences (mean ± 2 standard deviations) were −4 ± 14 mL/min/100 g in the young subjects and 6 ± 12 mL/min/100 g in the elderly subjects. Young subjects showed higher values than the elderly subjects for pCBF(PCMRI) (young, 57 ± 8 mL/min/100 g; elderly, 54 ± 7 mL/min/100 g; P = .05) and pCBF(ASL) (young, 61 ± 10 mL/min/100 g; elderly, 48 ± 10 mL/min/100 g; P < .001). CONCLUSIONS: The limits of agreement were too wide for the arterial spin-labeling method to be considered satisfactorily accurate, whereas the systematic overestimation in the young subjects and underestimation in the elderly subjects were close to acceptable. The age-related decrease in parenchymal CBF was augmented in arterial spin-labeling compared with phase-contrast MR imaging.